2017
DOI: 10.1051/matecconf/201712300001
|View full text |Cite
|
Sign up to set email alerts
|

Welding of titanium alloys

Abstract: Abstract. This article briefly summarises previous reports as well as some recent results on welding of various titanium alloys. Titanium is available in a wide range, hence, their properties and characteristics (including welding characteristics) may also varied significantly. The alloys studied represented three major areas; they are (1): unalloyed or commercially pure titanium (CP Ti), (2): near α and α+β alloys, and (3): β alloys. From our preliminary results, it can be reported that the structure of fusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
4
8
0
Order By: Relevance
“…In the present study, corresponding hardness also decreased somewhat inconsistently, as shown in Tables 3 and 4, and only varied by ~7%. Similar results for tensile property variation with acicular alpha-prime/alpha content have also been observed for both variously welded Ti-6Al-4V [28,29], as well as laser (SLM) and electron beam (EBM) processing and heat treatment of Ti64 [7,9,10], where additional anomalies and superior ductility have been achieved by the post-heat-treatment processing.…”
Section: Mechanical Property Measurements and Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In the present study, corresponding hardness also decreased somewhat inconsistently, as shown in Tables 3 and 4, and only varied by ~7%. Similar results for tensile property variation with acicular alpha-prime/alpha content have also been observed for both variously welded Ti-6Al-4V [28,29], as well as laser (SLM) and electron beam (EBM) processing and heat treatment of Ti64 [7,9,10], where additional anomalies and superior ductility have been achieved by the post-heat-treatment processing.…”
Section: Mechanical Property Measurements and Discussionsupporting
confidence: 74%
“…In the present study, corresponding hardness also decreased somewhat inconsistently, as shown in Tables 3 and 4, and only varied by ~7%. Similar results for tensile property variation with acicular alphaprime/alpha content have also been observed for both variously welded Ti-6Al-4V [28,29], as well as laser (SLM) and electron beam (EBM) processing and heat treatment of Ti64 [7,9,10], where additional anomalies and superior ductility have been achieved by the post-heat-treatment processing. It is apparent upon examining and comparing Tables 3 and 4, along with a somewhat systematic perusal of the comparative microstructure images in Figures 4-9, that there is a complex interplay between the grain structure (grain size) and the intragrain microstructures: acicular alpha-prime and alpha, including the contributions of bcc beta phase.…”
Section: Mechanical Property Measurements and Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The epitaxial growth is demonstrated by all primary grains solidifying at the weld-metal interface, providing a competitive growth rate resulting in a coarse-grained microstructure at the center of the MZ4. Such similar epitaxial growth is explained in 54,55 and the epitaxial layer is clearly visible in Figure 7(d).…”
Section: Microstructure Of the Weld Zone Of The Welded Jointsupporting
confidence: 80%
“…Typical yield strength ranged from 170 to 480 MPa. It came from the strengthening elements, i.e., oxygen and nitrogen in the form of α-phase accompanied by some minor β-phase due to the presence of Fe [13][14][15]. To date, under optimum processing conditions, the strength of the laser-welded titanium alloys can be close to that of the original material [16].…”
Section: Introductionmentioning
confidence: 99%